1990
DOI: 10.3758/bf03211531
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol impairs visual presence/absence detection more for females than for males

Abstract: Ninety subjects (45 males, 45 females) were given 0.0, 0.5, or 1.0 ml/kg body weight of 190-proofethanol and tested for chance-level presence/absence detection thresholds with energy-masked presentations of traffic signs and blank inputs. Alcohol produced higher blood alcohol concentration (BAC) levels, and higher detection threshold durations, for females than for males. These results indicate that alcohol influences precortical visual processing and that the influence is greater for females than for males. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In contrast, in humans, men binge drink more often and in greater excess than women. However, women have smaller gastric ethanol metabolism and less body water volume than men (Marshall et al, 1983; Baraona et al, 2001), leading to higher BECs and greater behavioral effects from the same dose of acute ethanol (Avant, 1990; Frezza et al, 1990; Ammon et al, 1996). As such, women are far more likely to become impaired, suffer greater organ and morphological brain changes, and develop comorbid medical conditions from ethanol consumption (Krasner et al, 1977; Eckardt et al, 1981; Urbano-Marquez et al, 1995; Key et al, 2006; Medina et al, 2008; Squeglia et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in humans, men binge drink more often and in greater excess than women. However, women have smaller gastric ethanol metabolism and less body water volume than men (Marshall et al, 1983; Baraona et al, 2001), leading to higher BECs and greater behavioral effects from the same dose of acute ethanol (Avant, 1990; Frezza et al, 1990; Ammon et al, 1996). As such, women are far more likely to become impaired, suffer greater organ and morphological brain changes, and develop comorbid medical conditions from ethanol consumption (Krasner et al, 1977; Eckardt et al, 1981; Urbano-Marquez et al, 1995; Key et al, 2006; Medina et al, 2008; Squeglia et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study reported that alcohol increased the detection thresholds for visual stimuli to a greater degree in women compared with men (e.g. Avant, 1990). Studies of alcohol effects on short-and long-term memory also report that women display greater alcohol-induced impairments of immediate and delayed recall compared with their male counterparts Jones, 1976, 1977;Niaura et al, 1987;Haut et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Hindmarch et al (1991), using a cognitivebehavioral battery of tests, found males more impaired than females on some tasks, with no differences in other tasks. In contrast, Avant (1990) found that females were more impaired by alcohol in a visual detection task than males. Cherpitel (1996) reported that whereas 3109 alcohol-related emergency-room visits were more frequently violence-related among men, a greater proportion of women compared to men suffered injuries related to falls or motor vehicle accidents.…”
Section: Discussionmentioning
confidence: 74%